2014
DOI: 10.3233/jad-141179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Therapeutic Educational Program on Quality of Life in Alzheimer's Disease: Results of a Pilot Study

Abstract: This study revealed a significant positive impact of a therapeutic educational program on patients' quality of life. Our results led us to design a randomized controlled trial called the THERAD study (THERapeutic education in Alzheimer's disease). It started in January 2013, and the results will be available in 2015. If the efficacy of this approach is proven, it will be important to implement educational programs in the care plan of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
2
3
0
2
Order By: Relevance
“…This finding is also in agreement with [18], France, who reported a significant positive effect of a therapeutic educational program on patients' life and that of their caregivers. As well [19], Canada, who indicated that, significant improvement on the posttest participants' attitudes, practices, confidence, and knowledge [14], emphasized that the highest percentage of nurses' knowledge were unsatisfactory and immediately improved after implementation of the guidelines.…”
Section: Discussion Of the Study Findings Are Categorized Under The Fsupporting
confidence: 92%
“…This finding is also in agreement with [18], France, who reported a significant positive effect of a therapeutic educational program on patients' life and that of their caregivers. As well [19], Canada, who indicated that, significant improvement on the posttest participants' attitudes, practices, confidence, and knowledge [14], emphasized that the highest percentage of nurses' knowledge were unsatisfactory and immediately improved after implementation of the guidelines.…”
Section: Discussion Of the Study Findings Are Categorized Under The Fsupporting
confidence: 92%
“…Physical exercise reduced neuropsychiatric symptoms in patients with mild dementia [64]. A program of therapeutic education for patients and caregivers improve the quality of life [65]. Finally, multicomponent programs have been shown to improve apathy, anxiety, depression, and quality of life [66].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a sample size estimation based on the existing literature [ 31 , 32 ] and a pilot study we previously carried out [ 33 ]. The size was initially 170 dyads; however, during data monitoring, an unexpected 11% of unexploitable data for the primary outcome led us to include 26 additional dyads.…”
Section: Methodsmentioning
confidence: 99%